Франция во Второй мировой войне - Гадеев, А.В. (Культура народов Причерноморья, 2014)
В статье дается анализ войны фашистской Германии с Францией. Франция имея значительные военные силы не смогла противостоять противнику. В развертывании германской армии преобладала идея наступления. На направлении главного удара в Арденнах немцы создали трехкратное превосходство, прежде всего в мобильных танковых соединениях. В их использовании немцы обладали серьезным тактическим преимуществом. Немецкие танки были сведены в крупные самостоятельные соединения (дивизии), что обеспечивало возможность их массированного применения. У статті дається аналіз війни фашистської Німеччини з Францією. Франція маючи значні військові сили не змогла протистояти противнику. У розгортанні німецької армії переважала ідея наступу. На напрямку головного удару в Арденнах німці створили триразову перевагу, перш за все у мобільних танкових з'єднаннях. Щодо їх використання німці мали серйозну тактичну перевагу. Німецькі танки були зведені у великі самостійні з'єднання (дивізії), що забезпечувало можливість їх масового застосування. In the article the analysis of the war, Nazi Germany with France. France has a significant military forces were not able to resist the enemy. In the deployment of the German army was dominated by the idea offensive. On the direction of the main attack in the Ardennes Germans created a three-fold superiority, particularly in the mobile tank connections. Using them, the Germans had serious tactical advantage. The German tanks were consolidated into a large independent connection (division), which ensured the possibility of massive use. The reasons overdue world conflict was rooted in the desire of Germany to obtain additional sources of raw materials and sales markets, which at that time was controlled by Britain, France and Russia. To achieve these objectives, Germany sought to defeat these powers and grab the colony from England to France and the Western lands of Russia (Poland, Baltic States, Ukraine, Belarus).